Mathematical Analysis and Applications II - Srivastava, Hari Mohan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This issue is a continuation of the previous successful Special Issue “Mathematical Analysis and Applications” <https://www.mdpi.com/journal/axioms/special_issues/mathematical_analysis>. Investigations involving the theory and applications of mathematical analytical tools and techniques are remarkably widespread in many diverse areas of the mathematical, physical, chemical, engineering and statistical sciences. In this Special Issue, we invite and welcome review, expository and original research articles dealing with the recent advances in mathematical analysis and its multidisciplinary applications.